Supporting Tourism Development Through Creative Economy Clusters in Lebak District - Shofi Elmia, Arini (Politeknik Pariwisata NHI Bandung, 2023)
The presence of materials and human resources in the Lebak Regency supports the creation of creative products in this district. However, this potential has not been maximized due to the undeveloped industrial system to support the development of the creative economy. Various causes of the underdeveloped potential and resources of tourism and the creative economy in Lebak Regency are due to the undeveloped industrial structure that supports the development of the creative economy, the unavailability of financing schemes for the creative economy industry players, limited access to marketing for the creative economy and not yet optimal institutional support for the creative economy as well as the large area of Lebak Regency. Creating strategic development is crucial for the future. One form of regional development is through the development of economic clusters. Creative economic cluster is necessary to formulate a development concept and strategy for Lebak Tourism Development. This study uses a SWOT analysis to help formulate a plan or strategy for an organization or a particular practice in a systematic way. The data used in this study are primary data through interviews, questionnaires, field observations, and documentation. Secondary data were obtained through literature studies, government policy documents, government agencies reports, and other media, also both mass media and the Internet. The result formulated 4 strategies for creative economic cluster development, namely (1) Creating creative economy clusters, divided into the north, middle, and south clusters; (2) Creating a tourism village in each cluster based on its creative economy potential; (3) Creating an institutional scheme for developing the creative economy; and (4) Creating project bundling in each cluster.